Dual-Energy CTA in Patients with Symptomatic Peripheral Arterial Occlusive Disease: Study of Diagnostic Accuracy and Impeding Factors - Klink, Thorsten; Wilhelm, Theresa; Roth, Christine; Heverhagen, Johannes T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The purpose of this study was to assess the diagnostic performance of dual-energy CT angiography (DE-CTA) in patients with symptomatic peripheral artery occlusive disease (PAOD) and to identify factors that impede its diagnostic accuracy.Materials and Methods Dual-source DE-CTA scans of the lower extremities of 94 patients were retrospectively compared to the diagnostic reference standard, digital subtraction angiography (DSA). Two independent observers assessed PAOD incidence, image quality, artifacts, and diagnostic accuracy of DE-CTA in 1014 arterial segments on axial, combined 80/140 kVp reconstructions and on 3 D maximum intensity projections (MIP) after automated bone and plaque removal. The impact of calcifications, image quality, and image artifacts on the diagnostic accuracy was evaluated using Fisher’s exact test. Furthermore, interobserver agreement was analyzed.Results Two observers achieved sensitivities of 98.0 % and 93.9 %, respectively, and specificities of 75.0 % and 66.7 %, respectively, for detecting stenoses of > 50 % of the lower extremity arteries. Calcifications impeded specificity, e. g. from 81.2 % to 46.2 % for reader 1 (p < 0.001). Specificity increased with higher image quality, e. g. from 70.0 % to 76.4 % for reader 1 (p < 0.001). Artifacts decreased the specificity of reader 2 (p < 0.001). The overall interobserver agreement ranged between moderate and substantial for stenosis detection and calcified plaques.Conclusion DE-CTA is accurate in the detection of arterial stenoses of > 50 % in symptomatic PAOD patients. Calcified atherosclerotic plaques, image quality, and artifacts may impede specificity.Key Points: Citation Format
Keywords: vascular; CT angiography; dual-energy computed tomography angiography; peripheral artery occlusive disease; critical limb ischemia